2021
DOI: 10.1108/jtf-10-2020-0171
|View full text |Cite
|
Sign up to set email alerts
|

Prioritizing the barriers to tourism growth in rural India: an integrated multi-criteria decision making (MCDM) approach

Abstract: PurposeTourism is one of the upcoming service industry in India with high potentials for future growth, particularly in rural areas. Many potential barriers are affecting the growth of tourism in rural India. Therefore, it is essential to explore and prioritize the barriers to tourism growth in rural India.Design/methodology/approachQualitative and quantitative responses from “16” experts related to tourism and hospitality management from central India are collected for this study. An integrated Multi-Criteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…However, the region faces other challenges, particularly in terms of infrastructural amenities for the tourism industry, which are also mentioned by tourism service providers in their remarks. A recent study on barriers to tourism growth by Jena and Dwivedi (2021) found “insufficient investment in tourism” as the controlling barrier to tourism development. They placed lack of access and connectivity as a shallow influencing barrier while in this study we have found lack of a sound transportation system and lack of connectivity as the primary barriers to tourism development.…”
Section: Discussionmentioning
confidence: 99%
“…However, the region faces other challenges, particularly in terms of infrastructural amenities for the tourism industry, which are also mentioned by tourism service providers in their remarks. A recent study on barriers to tourism growth by Jena and Dwivedi (2021) found “insufficient investment in tourism” as the controlling barrier to tourism development. They placed lack of access and connectivity as a shallow influencing barrier while in this study we have found lack of a sound transportation system and lack of connectivity as the primary barriers to tourism development.…”
Section: Discussionmentioning
confidence: 99%
“…However, the effect in terms of magnitude is more pronounced for High-Income Countries (HIC) and Upper Middle-Income Countries (UMIC), which alludes to structural differences between these groups that make globalization more effective. These differences may include better security provisions, improved and more flexible tourist mobility, or a greater policy focus on enhancing tourism (Fereidouni et al, 2014;Jena & Dwivedi, 2021). A similar tendency was apparent in the case of the de-facto measure of globalization, i.e., the state of globalization tends to have a significant positive effect on the tourism trade balance.…”
Section: Resultsmentioning
confidence: 82%
“…Out of the twenty, only thirteen experts agreed to participate in the study. Past MCDM studies suggest that the number of experts should be between 5 and 50 for good decision-making (Aghasafari et al, 2020;Jena and Dwivedi, 2021;Nguyen, 2022). The details of the experts are given in Table A1 in Appendix.…”
Section: Methodsmentioning
confidence: 99%